Pemanfaatan Media Sosial Sebagai Media Pembelajaran Pendidikan Agama Islam - Sajdah, Meilisa; Dwistia , Halen (Ar-Rusyd: Jurnal Pendidikan Agama Islam, 2022)
This research is to determine the impact of the implementation of social media as a learning media in particular. Field facts where the use of social media in the form of the internet in Indonesia shows that the development of technology has progressed rapidly. Not a few schools and universities in Indonesia that utilize technological advances as one of the media in learning, one of which is Islamic religious education. The author then by applying qualitative method, with a literature study examines the impact of the use of social media in learning Islamic religious education, both about positive and negative effects. This is also motivated by the use of social media which is recently used by students. Social media has a positive influence on socialization among its users but can also have a bad effect in real life. This then causes changes in the ability of children in learning and understanding the teaching material of Islamic religious education, both in the form of academic abilities or personality.